A young Moon-forming giant impact at 70-110 million years accompanied by late-stage mixing, core formation and degassing of the Earth. - Halliday, A (2008)
New W isotope data for lunar metals demonstrate that the Moon formed late in isotopic equilibrium with the bulk silicate Earth (BSE). On this basis, lunar Sr isotope data are used to define the former composition of the Earth and hence the Rb-Sr age of the Moon, which is 4.48+/-0.02Ga, or 70-110Ma (million years) after the start of the Solar System. This age is significantly later than had been deduced from W isotopes based on model assumptions or isotopic effects now known to be cosmogenic. The Sr age is in excellent agreement with earlier estimates based on the time of lunar Pb loss and the age of the early lunar crust (4.46+/-0.04Ga). Similar ages for the BSE are recorded by xenon and lead-lead, providing evidence of catastrophic terrestrial degassing, atmospheric blow-off and significant late core formation accompanying the ca 100Ma giant impact. Agreement between the age of the Moon based on the Earth's Rb/Sr and the lead-lead age of the Moon is consistent with no major losses of moderately volatile elements from the Earth during the giant impact. The W isotopic composition of the BSE can be explained by end member models of (i) gradual accretion with a mean life of roughly 35Ma or (ii) rapid growth with a mean life of roughly 10Ma, followed by a significant hiatus prior to the giant impact. The former assumes that approximately 60 per cent of the incoming metal from impactors is added directly to the core during accretion. The latter includes complete mixing of all the impactor material into the BSE during accretion. The identical W isotopic composition of the Moon and the BSE limits the amount of material that can be added as a late veneer to the Earth after the giant impact to less than 0.3+/-0.3 per cent of ordinary chondrite or less than 0.5+/-0.6 per cent CI carbonaceous chondrite based on their known W isotopic compositions. Neither of these on their own is sufficient to explain the inventories of both refractory siderophiles such as platinum group elements and rhenium, and volatiles such as sulphur, carbon and water.